Analisis Penerapan Sistem Informasi Manajemen dalam Meningkatkan Efisiensi Operasional dan Daya Saing Citra Swalayan Muaro di Era Digital - Buswir, Amille Cantika; Dewantara, Masgar; Kumbara, Vicky Brama (Indo-MathEdu Intellectuals Journal, 2026)
The development of information technology in the digital era encourages the retail sector to optimize the use of Management Information Systems (MIS) to improve operational efficiency and competitiveness. Citra Swalayan Muaro, as one of the local retail businesses, faces increasingly intense competition and therefore requires an integrated and accurate information management system to support transaction processes, inventory management, and the preparation of reports quickly and accurately. This study employs a qualitative approach with a case study method to analyze the implementation of the existing system. Data were collected through interviews, observations, and documentation, and then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of MIS is able to increase transaction speed, minimize errors in stock recording, and provide more accurate and real-time sales information. This improvement in operational efficiency contributes to strengthening competitiveness through more responsive services, more effective cost control, and data-based decision making. However, system optimization still requires improved integration between departments and the strengthening of human resource competencies so that the use of technology can be maximized.